Elaboração de protocolo eletrônico de gerenciamento de aceleradores lineares contemplados pelo plano de expansão da radioterapia no SUS (PER-SUS) - Maia, France Anne Reinaldo (2020)
The aim of this study is to propose an application for the management of linear accelerators, with the pilot Fundação Hospital Assistencial da Paraíba (FAP), the first service favored by the Plano de Expansão da Radioterapia no Sistema Único de Saúde (PER-SUS). The linear accelerator is a high-tech and high-cost electromedical equipment, both for acquisition and maintenance, and in view of the contingency of financial resources for health, an effective management of this essential resource in cancer treatment is necessary. To assist in the survey of the requirements addressed in the protocol, an integrative review was carried out on the topic of management of medical equipment and health management, documents analysis and visit to the radiotherapy servisse of the FAP, in Campina Grande -PB.The proposed web system is made using the client-server model, the server part being divided into two: front-end and back-end. The front-end was developed in Javascript®, using the React framework and hosted on the Netlify® platform. The back-end was also developed in Javascript®, running on the Node® interpreter and hosted on the Heroku® platform. In this system, the registration and editing of information and files related to the device's inventory, maintenance, calibrations and accessories of one or more machines can be performed, the files being hosted on a Google® file upload service, Google Cloud Storage®. With this work, it is concluded that the proposal of a multiplatform and 100% web application, with the piloto of the FAP hospital, for the management of linear accelerators provided by the Plano de Expansão da Radioterapia no SUS (PER-SUS), will help in the improvement the quality of the servisse providede to the population, as it enables management solutions for these devices, prioritizing corrective and preventive maintenance.